Arctic Pollution Issues: A State of the Arctic Environment Report. - Arctic Monitoring and Assessment Programme (AMAP) (AMAP Secretariat, 1997)
A condensed version of the 1998 AMAP Assessment (scientific/technical ) Report, presenting the information in a clear and readable manner for the non-scientific audience; richly illustrated and prefaced by an Executive Summary with recommendations specifically addressed to Ministers of the eight Arctic countries.